Implications of energy efficient Ethernet for hubs and switches. (6th December 2010) - Reviriego, P.; Maestro, J.A.; Bleakley, C.J.
The efficient use of energy in communications is an area of growing interest. Until recently energy efficiency received little attention in most wireline communications standards and implementations. In many cases, the transmitter and receiver operate at full power, even when no data is being sent. This is the case in most wireline Ethernet standards that results in a considerable waste of energy. Efforts are now underway to develop new standards, such as energy efficient Ethernet, with the aim of reducing energy consumption. The changes introduced by energy efficient Ethernet have different implications for each network element. The implications for hubs are different to those for switches. These implications are analysed in this paper. It is shown that the adoption of the new standard will make hubs less energy efficient than switches. The implications studied in this paper illustrate the potential impact of energy efficient Ethernet on Ethernet networks.